Optical reading of contaminants in aqueous media based on gold nanoparticles - Du, Jianjun (2014)
With increasing trends of global population growth, urbanization, pollution over-exploitation, and climate change, the safe water supply has become a global issue and is threatening our society in terms of sustainable development. Therefore, there is a growing need for a water-monitoring platform with the capability of rapidness, specificity, low-cost, and robustness. This review summarizes the recent developments in the design and application of gold nanoparticles (AuNPs) based optical assays to detect contaminants in aqueous media with a high performance. First, a brief discussion on the correlation between the optical reading strategy and the optical properties of AuNPs is presented. Then, we summarize the principle behind AuNP-based optical assays to detect different contaminants, such as toxic metal ion, anion, and pesticides, according to different optical reading strategies: colorimetry, scattering, and fluorescence. Finally, the comparison of these assays and the outlook of AuNP-based optical detection are discussed.